An explorative study on how needle exchange programme service users construct health : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology - Health Psychology Subject, at Massey University, Albany, New Zealand - Knudsen, Zoe Frances (Massey University, 2026)
Needle Exchange Programmes (NEPs) are a social initiative, where people who inject drugs (PWID) are able to access sterile injecting equipment and safely dispose of used needles. NEPs use harm reduction principles to reduce the poor health outcomes that can result from practices such as needle sharing and reusing. There is an assumption that PWID do not care about their health, which is linked to neoliberal ideas of health and morality regarding individual choices and their health. There is some evidence that shows, contrary to popular belief, PWID do care about their health. The current research project had two aims: firstly, to understand how Needle Exchange Program (NEP) users construct their health; and, secondly, to explore how, according to service users, the NEP contributes to service users’ overall health. Participants were six service users of an Aotearoa New Zealand, South Island NEP outlet store. All participants identified as Pākehā/NZ European, and five identified as male, with one participant not disclosing their gender. Interviews were conducted on the premise of a South Island NEP outlet store. Reflexive Thematic Analysis was used to analyse the transcribed interviews and three themes were produced:1) PWID constructions of health and health practices; 2) Social factors and health; and 3) The NEPs contribution to health. Participants overwhelmingly felt that health was an individual responsibility, in accordance with neoliberal beliefs, and they engaged in daily practices, such as mindful nutrition consumption, to maintain a good health citizen status. Participants also framed their injecting drug use as a positive health behaviour which benefited their health maintenance. Despite describing health as an individual responsibility, participants still acknowledged external factors as impacting their health. The experience of stigma negatively affected participants through creating barriers to health access, whereas important relationships contributed positively to their health. Finally, the NEP was a significant contributor to the health of participants, through enabling positive physical health, and through the relational support provided.
Keywords: 520304 Health psychology